Two-dimensional Model of Ciliwung River Flood in DKI Jakarta for Development of the Regional Flood Index Map - Adam FormÃ¡nek; Rasmiaditya Silasari; M. Syahril Badri Kusuma; Hadi Kardhana (Institute for Research and Community Services, Institut Teknologi Bandung, 2013)
The objective of this study was to present a sophisticated method of developing supporting material for flood control implementation in DKI Jakarta. High flow rates in the Ciliwung River flowing through Jakarta regularly causes extensive flooding in the rainy season. The affected area comprises highly densely populated villages. For developing an efficient early warning system in view of decreasing the vulnerability of the locations a flood index map has to be available. This study analyses the development of a flood risk map of the inundation area based on a two-dimensional modeling using FESWMS. The reference event used for the model was the most recent significant flood in 2007. The resulting solution represents flood characteristics such as inundation area, inundation depth and flow velocity. Model verification was performed by confrontation of the results with survey data. The model solution was overlaid with a street map of Jakarta. Finally, alternatives for flood mitigation measures are discussed.